Effects of ketamine on brain function during smooth pursuit eye movements. Issue 11 (6th October 2016) - Steffens, M.; Becker, B.; Neumann, C.; Kasparbauer, A.M.; Meyhöfer, I.; Weber, B.; Mehta, M.A.; Hurlemann, R.; Ettinger, U.
Abstract: The uncompetitive NMDA receptor antagonist ketamine has been proposed to model symptoms of psychosis. Smooth pursuit eye movements (SPEM) are an established biomarker of schizophrenia. SPEM performance has been shown to be impaired in the schizophrenia spectrum and during ketamine administration in healthy volunteers. However, the neural mechanisms mediating SPEM impairments during ketamine administration are unknown. In a counter‐balanced, placebo‐controlled, double‐blind, within‐subjects design, 27 healthy participants received intravenous racemic ketamine (100 ng/mL target plasma concentration) on one of two assessment days and placebo (intravenous saline) on the other. Participants performed a block‐design SPEM task during functional magnetic resonance imaging (fMRI) at 3 Tesla field strength. Self‐ratings of psychosis‐like experiences were obtained using the Psychotomimetic States Inventory (PSI). Ketamine administration induced psychosis‐like symptoms, during ketamine infusion, participants showed increased ratings on the PSI dimensions cognitive disorganization, delusional thinking, perceptual distortion and mania. Ketamine led to robust deficits in SPEM performance, which were accompanied by reduced blood oxygen level dependent (BOLD) signal in the SPEM network including primary visual cortex, area V5 and the right frontal eye field (FEF), compared to placebo. A measure of connectivity with V5 and FEF as seed regions, however, was not significantly affected by ketamine. These results are similar to the deviations found in schizophrenia patients. Our findings support the role of glutamate dysfunction in impaired smooth pursuit performance and the use of ketamine as a pharmacological model of psychosis, especially when combined with oculomotor biomarkers. Hum Brain Mapp 37:4047–4060, 2016 . ©2016 Wiley Periodicals, Inc .